Listening through Webs for/of Creole Improvisation: Weaving Music II as a Case Study - Cox, Jessie; Yulsman, Sam (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Our paper reflects on our experience with Weaving Music II—a web performance space we built with fifteen artists working across different disciplines. The website and our essay attempt to create alternatives to the “at-the-same-timeness” of streaming technologies as well as the forms of listening defined by data capitalism and corporate platforms like Google and YouTube. At the heart of the alternative practices we propose is an embrace of what we see as the creolizing potentiality of the Web and of listening. To unpack these potentialities, the essay and artwork critically reflect on listening that occurs through  Afrofuturistic modes of engagement with technology, space and time. We consider the historical origins of Web improvisations, our approach to collaboration using Weaving Music II, and theories of information that move beyond the need for predefined codes of understanding.